Experience of Gastrostomy Using a Quality Care Framework: The Example of Rett Syndrome - Downs, Jennepher; Wong, K.; Ravikumara, M.; Ellaway, C.; Elliott, E.; Christodoulou, J.; Jacoby, P.; Leonard, H. (Lippincott Williams & Wilkins, 2014)
Rett syndrome is one of many severe neurodevelopmental disorders with feeding difficulties. In this study, associations between feeding difficulties, age, MECP2 genotype, and utilization of gastrostomy were investigated. Weight change and family satisfaction following gastrostomy were explored. Data from the longitudinal Australian Rett Syndrome Database whose parents provided data in the 2011 family questionnaire (n = 229) were interrogated. We used logistic regression to model relationships between feeding difficulties, age group, and genotype. Content analysis was used to analyze data on satisfaction following gastrostomy. In those who had never had gastrostomy and who fed orally (n = 166/229), parents of girls <7 years were more concerned about food intake compared with their adult peers (odds ratio [OR] 4.26; 95% confidence interval [CI] 1.29, 14.10). Those with a p.Arg168* mutation were often perceived as eating poorly with nearly a 6-fold increased odds of choking compared to the p.Arg133Cys mutation (OR 5.88; 95% CI 1.27, 27.24). Coughing, choking, or gagging during meals was associated with increased likelihood of later gastrostomy. Sixty-six females (28.8%) had a gastrostomy, and in those, large MECP2 deletions and p.Arg168* mutations were common. Weight-for-age z-scores increased by 0.86 (95% CI 0.41, 1.31) approximately 2 years after surgery. Families were satisfied with gastrostomy and felt less anxious about the care of their child. Mutation type provided some explanation for feeding difficulties. Gastrostomy assisted the management of feeding difficulties and poor weight gain, and was acceptable to families. Our findings are likely applicable to the broader community of children with severe disability.